2005
DOI: 10.1002/cbf.1312
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of caffeic acid phenethyl ester (CAPE) against liver damage induced by cigarette smoke inhalation in rats

Abstract: The aim of this study was to investigate the histological and biochemical changes in liver of rats exposed to cigarette smoke and effects of caffeic acid phenetyl ester (CAPE) on these changes. For this purpose, 21 male Wistar rats were divided into three groups. Animals in Group I were used as control. Rats in Group II were exposed to cigarette smoke and rats in Group III were exposed to cigarette smoke and injected daily with CAPE. At the end of the 60-days experimental period, all rats were killed by decapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…to 12 weeks old female Wistar albino rats (10 μmol/kg body mass; 6-days administration), prevented cisplatin-induced oxidative changes in the liver by reducing ROS production and increasing antioxidative enzyme activities (such as SOD, GSH-Px and CAT) [24]. Caffeic acid phenethyl ester also revealed the protective effects against liver damage induced by cigarette smoking [25], amikacin-induced nephrotoxicity [26] and methotrexate-induced hepatorenal oxidative injury [27]. …”
Section: Discussionmentioning
confidence: 99%
“…to 12 weeks old female Wistar albino rats (10 μmol/kg body mass; 6-days administration), prevented cisplatin-induced oxidative changes in the liver by reducing ROS production and increasing antioxidative enzyme activities (such as SOD, GSH-Px and CAT) [24]. Caffeic acid phenethyl ester also revealed the protective effects against liver damage induced by cigarette smoking [25], amikacin-induced nephrotoxicity [26] and methotrexate-induced hepatorenal oxidative injury [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Caffeic acid derivatives are potent antioxidants and have shown some protective effects in CS-exposed rats and rabbits (19,46,55). Caffeic acid is also a potent inhibitor of 5-LO (26), which is upregulated in COPD patients (21,27).…”
Section: L168 Inhibitors Of Acute Cigarette Smoke-induced Inflammationmentioning
confidence: 99%
“…CAPE has been widely accepted as a hepatoprotective folk medicine for many years. Its protective effects are attributed to its cytoprotective, anti-oxidant, antiproliferative, and anti-inflammatory effects, and it has been shown to inhibit both lipoxygenase activity and lipid peroxidation [3][4][5][6][7][8][9] . CAPE can also inhibit phorbol ester-induced H2O2 production and tumor promotion [10,11] , and it was reported that many CAPE activities were related to transcription factor inhibition of nuclear factor-kappa B (NF-κB) [10,[12][13][14] .…”
Section: Introductionmentioning
confidence: 99%